RESEARCH VISIBILITY OF FACULTY MEMBERS OF NAVRACHANA UNIVERSITY ON RESEARCH GATE - Pandya, Rucha; Vyas, Meghna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Study highlights the function of academic social networking sites in promoting research dissemination and collaboration by looking at the research visibility of Navrachana university faculty members on ResearchGate (RG). By analysing the profiles of 49 faculty members of Navrachana University across five disciplines such as Science, engineering and technology, Liberal Studies & Education, Business and Law, and Environmental Design and Architecture. The evaluation results shows that Science has highest articles 232 and the RG Score 2173.4, followed by Engineering & Technology. Liberal Studies and education prove notably strong engagement high reads and recommendations, led by Faculty Dr.Rishi Raj Balwaria. However, there is limited involvement and exposure in the Business and Law, Environmental Design and Architecture. The study Emphasizes how ResearchGate (RG) may create a global academic community by overcoming geographical and institutional boundaries.